Remembering Christiaan Barnard in Philately - Hosain, Nazmul; Anisuzzaman, Md (Cardiovascular Journal, 2023)
Christiaan Barnard is famous for his legendary operation of first ever successful human heart transplantation performed on December 3, 1967 at the Groote Schuur hospital Cape Town, South Africa. The operation captured the World public imagination as no surgical procedure had ever before or since. Christian Barnard, a little known surgeon from apartheid South Africa suddenly became the focus of media attention. The Groote Schuur team captured the headlines of the world’s leading newspapers. However, forgotten are the names of those innumerable surgeons, cardiologists, basic scientists and researchers whose research works paved the pathway to transplant success. It may be difficult to estimate the level of world’s interest about the action of Christiaan Barnard and his team. One example is a commemorative postal stamp published to honor him by countries from different parts of the world. They include Bhutan, St. Helena, Romania, Commonwealth of Dominica, Mozambique and Republic of Congo and others. Yemen Arab Republic printed a series of stamps honoring Dr. Christiaan Barnard. African country Guine Bissau printed a beautiful stamp and first day coverportraying Barnard and a beautiful image of a little girl on a hospital bed with the teddy bear in her arms.Latin American country Paraguay gave Dr. Barnard a distinct honor by portraying him on a series along with Reverend Martin Luther King & President John F Kennedy. Christiaan Barnard was among the most celebrity surgeons of the world. Many countries have printed commemorative stamps to respect and celebrate his achievement. Ironically, many of these countries lack even the basic cardiac surgical facilities. Cardiovasc j 2023; 16(1): 53-55